2017
DOI: 10.1002/app.45197
|View full text |Cite
|
Sign up to set email alerts
|

Polyethylene/sepiolite clay nanocomposites: Effect of clay content, compatibilizer polarity, and molar mass on viscoelastic and dynamic mechanical properties

Abstract: In this work, high-density polyethylene (HDPE)-based nanocomposites having different concentrations of Sepiolite (1-10 wt %) and compatibilizer, that is, PE-graft-maleic anhydride (PE-g-MA) of varying molecular weight and maleic anhydride content were prepared by melt compounding. The influence of Sepiolite amount and compatibilizer polarity and molar mass on the crystallization behavior [differential scanning calorimeter (DSC) and X-ray diffraction (XRD)], rheological properties (oscillatory rheometer) and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…In general, semi-crystalline polymers such as HDPE are regarded as a three-phase continuum composed of an amorphous phase, a crystalline phase, and an inter-phase. The crystalline skeleton is formed by mutually connected spherulites, each of them consist of a number of crystalline lamellae with an amorphous phase located in between the crystallites and lamellae [5,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…In general, semi-crystalline polymers such as HDPE are regarded as a three-phase continuum composed of an amorphous phase, a crystalline phase, and an inter-phase. The crystalline skeleton is formed by mutually connected spherulites, each of them consist of a number of crystalline lamellae with an amorphous phase located in between the crystallites and lamellae [5,[20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…a. The resistance to distortion under a given load can be used to define the heat deflection temperature (Singh, Vimal, Sharma, Kapur, & Choudhary, ). The PPI film containing 30% GLY quickly lengthens above 75 °C (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The peak observed was dissimilar to the literatures [16][17][18] , where it was mostly found at 2θ values of 7.3 -8.5°, corresponding to the to d 110 basal spacing. However, Singh et al 19 , has reported that the shifting of such peak may be presented if the sepiolite is heated at the temperature over 550°C. This may be possible as the sepiolite obtained was heated prior during mining process.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%
“…Apart from that, the peak intensity at 10.4° was more intense as increased the addition of sepiolite. This is associated to the higher amount of sepiolite which controls the crystal peak of sepiolite 19,20 . Figure 4 illustrates the curing curves of the sepiolite filled NR composites whereas the raw data obtained from the curing curves are also listed in Table 4.…”
Section: Scanning Electron Microscopymentioning
confidence: 99%